Development of Website Based Learning Media for Mathematical Modeling in The LPG Context to Support Mathematical Literacy Skills of Junior High School Students - Andita, Sintia; Darmawijoyo,; Somakim, (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
This study aims to develop website-based media for mathematical modeling with the Liquefied Petroleum Gas (LPG) context to support mathematical literacy skills. The method used is design research type development studies through Tessmer's formative evaluation flow, including self-evaluation, expert review, one-to-one, and small group. The product was evaluated in terms of validity and practicality. The expert validation results showed the media was very valid with a score of 4.38 in the media aspect and 4.25 in the material aspect. The practicality test at the small group stage obtained a score of 75.79 (practical category). The characteristics of the resulting media include: (1) valid media reviewed from the aspects of material, modeling, literacy, and display; (2) media that is practical to use in learning; (3) relevant and contextual media through the use of LPG as a real-world connection; (4) media that supports mathematical literacy skills through mathematical modeling structures; and (5) ease of navigation, automatic feedback, and communicative visual displays. Thus, the developed website-based media is proven to be valid, practical, and relevant to support students' mathematical literacy skills in small groups. In the pre-test stage, one student (16.7%) was classified in the medium category, while five students (83.3%) were in the low category. After the application of web-based mathematical modeling media, all six students (100%) achieved scores in the medium category. Abstrak: Penelitian ini bertujuan untuk mengembangkan media berbasis web untuk pemodelan matematika dengan konteks Gas Minyak Bumi Cair (LPG) untuk mendukung keterampilan literasi matematika. Metode yang digunakan adalah penelitian desain tipe pengembangan melalui alur evaluasi formatif Tessmer, termasuk evaluasi diri, tinjauan ahli, satu lawan satu, dan kelompok kecil. Produk dievaluasi dari segi validitas dan kepraktisan. Hasil validasi ahli menunjukkan media tersebut sangat valid dengan skor 4,38 pada aspek media dan 4,25 pada aspek materi. Uji kepraktisan pada tahap kelompok kecil memperoleh skor 75,79 (kategori praktis). Karakteristik media yang dihasilkan mencakup: (1) media yang valid ditinjau dari aspek materi, pemodelan, literasi, dan tampilan; (2) media yang praktis digunakan dalam pembelajaran; (3) media yang relevan dan kontekstual melalui penggunaan LPG sebagai keterkaitan dunia nyata; (4) media yang mendukung kemampuan literasi matematika melalui struktur pemodelan matematika; dan (5) kemudahan navigasi, umpan balik otomatis, serta tampilan visual yang komunikatif. Dengan demikian, media berbasis website yang dikembangkan terbukti valid, praktis, dan relevan untuk mendukung kemampuan literasi matematika siswa pada kelompok kecil yaitu Pada tahap pra-uji, satu siswa (16,7%) diklasifikasikan dalam kategori sedang, sedangkan lima siswa (83,3%) berada dalam kategori rendah. Setelah penerapan media pemodelan matematika berbasis web, keenam siswa (100%) mencapai skor dalam kategori sedang.